Optimal Placement of DG for Optimal Reactive Power Dispatch Using PSO Algorithm - o, Dsnmra; Kumar, Dr.Niranjan (International Journal of Engineering and Technology, 2018)
Â In the safety and economic point of view, Reactive Power is the most problematic thing during the operation of the electrical network. Reactive Power supply completion has nonlinear, equality and inequality constraints. Proposed work is carried out, to find the solution for reactive power supply issue, Particle Swarm Optimization (PSO) process as well as MATPOWER 5.1 implement package are developed in this process. PSO is an excellent optimization technique that is also having effective finding ability. One of the best assets of PSO is that its capacity is fewer sensitive than complication of the independent function. MAT POWER 5.1 is an undeveloped basis MATLAB implement package, concentrating the power flow issues findings. Suggested technique diminishes active power damage in the conventional power system and decides the optimum location of a newly setup Distributed Generator (DG). The IEEE 14bus arrangement is utilized to find the performance and test outcomes shown the perfectness of the recommended method.